Quality function deployment-based framework for the resilient supply chain - Yadav A.K.; Samuel C. (My University, 2025)
The concept of the resilient supply chain has appeared to be one of the essential tools to survive, compete and grow during disturbances and uncertainties. During the current pandemic and the Suez Canal blockage, this concept has once again proven its utility. In this research work, we explore the resilient supply chain’s concept, capabilities, and practices. In addition, an attempt is made to quantify the resilient performance of an Indian manufacturing organisation. For this research, we have used a quality function deployment integrated with the weighted sum method approach. This research brings about new insights into the concept of risk management through the resilient supply chain. It also suggests the portfolios of the resilient practices that enable the organisations to be prepared and recover from the major disruptions. Copyright © 2022 Inderscience Enterprises Ltd.